EFFECTS OF HIBISCUS SABDARIFFA L. CONSUMPTION DURING PREGNANCY ON BIOCHEMICAL PARAMETERS AND LITTER BIRTH WEIGHT IN RATS - Eghosa, Iyare E.; Charles, Ezeh O.; Thomas, Nubilla; Ifeoma, Orizu A. (African Journal of Traditional, Complementary and Alternative Medicines, 2015)
Background: Extracts of Hibiscus sabdariffa L. (HS; family: Malvaceae) are widely believed in folk medicine to be effective in the treatment ofa variety of ailments. In Nigeria, anecdotal reports by women who consume HS during pregnancy suggest that they consume it because of thefolkloric belief that it makes them “feel lighter”. This study aimed to investigate the effect of maternal consumption of HS during pregnancy onlitter birth weight and the functional integrity of the liver of pregnant rats.Materials and Methods: Thirty-six rats aged twelve to fourteen weeks were used. On day 1 of pregnancy, the rats were randomly assigned tothree groups. Group A were given tap water, group B were given 0.6g/100ml while group C were given 1.8g/100ml of the extract. On day 18 ofpregnancy, blood samples were taken for determination of Serum glutamate oxaloacetate transaminase (SGOT), serum glutamate pyruvatetransaminase (SGPT), alkaline phosphatase, urea and creatinine.Results: Gestational length, litter size and birth weights were recorded at delivery. HS consumption did not affect (P>0.05) SGOT level butincreased (P<0.05) the SGPT and decreased (P<0.05) ALP and creatinine levels. The low dose HS decreased (P<0.05) while the high dose HSincreased (P<0.05) the urea level. There was no significant (P>0.05) difference in the length of gestation but litter sizes and litter birth weightswere significantly (P<0.05) lower and higher respectively when compared with the control.Conclusion: We conclude that consumption of HS during pregnancy increases litter birth weight possibly through the gluconeogenic activitiesof the elevated SGPT.